2022
DOI: 10.1093/molbev/msac029
|View full text |Cite
|
Sign up to set email alerts
|

The Slowing Rate of CpG Depletion in SARS-CoV-2 Genomes Is Consistent with Adaptations to the Human Host

Abstract: Depletion of CpG dinucleotides in SARS-CoV-2 genomes has been linked to virus evolution, host-switching, virus replication, and innate immune responses. Temporal variations, if any, in the rate of CpG depletion during virus evolution in the host remain poorly understood. Here, we analysed the CpG content of over 1.4 million full-length SARS-CoV-2 genomes representing over 170 million documented infections during the first 17 months of the pandemic. Our findings suggest that the extent of CpG depletion in SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 39 publications
5
16
0
Order By: Relevance
“…If meaningless, then each of the six dinucleotide pairs should have the same mutation frequency (CG=GC, CT=TC, CA=AC, GA=AG, GT=TG, AT=TA). However, our results showed CG dinucleotides have a significantly higher mutation rate than GC dinucleotides (p < 0.01, t-test) (Figure S2 and Table 1), which is consistent with previous reports [34][35][36] . Since ZAP is able to specifically bind CpG dinucleotides in single-stranded RNA for targeted degradation, a reduction in the number of CG dinucleotides likely reflects an evasion mechanism resulting from virus evolution.…”
Section: Sequence Context Affects the Mutation Frequency Of Sars-cov-2supporting
confidence: 93%
“…If meaningless, then each of the six dinucleotide pairs should have the same mutation frequency (CG=GC, CT=TC, CA=AC, GA=AG, GT=TG, AT=TA). However, our results showed CG dinucleotides have a significantly higher mutation rate than GC dinucleotides (p < 0.01, t-test) (Figure S2 and Table 1), which is consistent with previous reports [34][35][36] . Since ZAP is able to specifically bind CpG dinucleotides in single-stranded RNA for targeted degradation, a reduction in the number of CG dinucleotides likely reflects an evasion mechanism resulting from virus evolution.…”
Section: Sequence Context Affects the Mutation Frequency Of Sars-cov-2supporting
confidence: 93%
“…Depletion of CpG dinucleotides in genomes of wild viruses from field samples has been linked to virus evolution, host-switching, pathogenicity, and innate immune responses ( 66 , 67 ). However, depletion of CpG dinucleotides in genomes of synthetic recoded viruses during in vivo infection is not well studied.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest a role for CpG depletion in shaping the evolution of HCV. Previous studies have shown that CpG depletion in virus genomes is pronounced during host adaptations [ 7 , 27 ]. In addition, CpG content remains stable for well-adapted human viruses such as influenza B virus [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of the CpG dinucleotides in viruses and their association with virus evolution and host-evasion strategies have been explored for both RNA [ 7 , 8 ] and DNA viruses [ 9 , 10 ]. The CpG content differs significantly amongst viruses [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation